1988
DOI: 10.1111/j.1468-2958.1988.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Plans and the Initiation of Social Relationships

Abstract: Reseaivchers interested in cognitive approaches to relational communication have typically sought explanations for how cognition influences the interpretation of social actions. Few attempts have been made to understand how cognitive structures guide action production. This study extends the work of such researchers by demonstrating the relationship of plans to two social outcomes, loneliness and shyness. College students described how they would request a date from a member of the opposite sex and how they wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 27 publications
0
61
1
1
Order By: Relevance
“…Berger's (1988aBerger's ( , 1988bBerger & Bell, 1988;) recent work on conversational planning demonstrates the currently ambivalent state of research opinion regarding the effects of planning knowledge on conversational performance. An investigation of compliance-gaining plans (Berger, 1988b) revealed that persons who could quickly access plan alternatives (i.e., alternative persuasive arguments) were more fluent in their presentation of persuasive messages.…”
Section: Conversational Planningmentioning
confidence: 92%
“…Berger's (1988aBerger's ( , 1988bBerger & Bell, 1988;) recent work on conversational planning demonstrates the currently ambivalent state of research opinion regarding the effects of planning knowledge on conversational performance. An investigation of compliance-gaining plans (Berger, 1988b) revealed that persons who could quickly access plan alternatives (i.e., alternative persuasive arguments) were more fluent in their presentation of persuasive messages.…”
Section: Conversational Planningmentioning
confidence: 92%
“…When asked to describe how they would initiate a romantic encounter with an opposite-sex partner, men are more likely than women to do so directly (e.g., by clearly asking for a date (Berger & Bell, 1988;Clark et al, 1999) rather than relying on more indirect strategies. The same pattern is evident in examinations of actual dating behavior.…”
Section: A Gender Difference In the Use Of Relationship Initiation Stmentioning
confidence: 99%
“…Recent work by Ayres (1992) confirms that high CA's have negative and disrupted information processing both when expecting to give a speech and after the speech has been completed. In a similar vein Berger and Bell (1989) found that high anxious students had more difficulty in developing social plans to approach or initiate contact with someone, than did their low anxious counterparts. Indeed it is not uncommon to hear anxious people say they worry about not having the right "opening line" or that something they say will "come out wrong."…”
Section: Measuring Communication Vs Performance Orientationmentioning
confidence: 64%